An experimental investigation on performances recovery of glass fiber reinforced composites exposed to a salt-fog/dry cycle. (15th May 2023) - Fiore, V.; Calabrese, L.; Miranda, R.; Badagliacco, D.; Sanfilippo, C.; Palamara, D.; Valenza, A.; Proverbio, E.
Abstract: The main goal of this paper is the evaluation of the properties reversibility of glass fiber reinforced polymers (GFRPs ) under discontinuous exposure to aggressive environmental conditions, typical of marine applications. To this aim, the GFRP manufactured through vacuum infusion process has been initially aged in humid conditions (i.e., exposure to salt-fog at 35 °C) for 15 and 30 days and then stored under controlled dry conditions (i.e., 50% R.H. and 23 °C) for times varying between 0 and 21 days. In order to evaluate the recover capability of this material, its water uptake has been monitored along the quasi-static flexural properties during the entire humid/dry cycle. Moreover, both 3D optical and scanning electron microscopes (SEM) have been used to analyze the morphology of fractured samples at different humid and dry times, thus correlating the properties evolution of the composite with its morphology. The main outcome of the present paper is an evident performances recovery shown by the investigated composite during the drying phase. Indeed, despite its flexural strength and modulus were reduced by about 20% and 10% after 30 days of salt-fog exposition, the GFRP composite evidenced a complete recovery of its initial mechanical performances after long drying times (i.e., 21 days). These findings clearly indicate that although some degradation phenomena occurred during the humid phase, their effects on both strength and stiffness of the investigated composite have proven to be mainly reversible. Highlights: A GFRP composite were exposed to a salt-fog/dry aging cycle. Flexural tests and water uptake measurements were performed. GFRP composite experienced mainly reversible degradative phenomena. GFRP composite showed complete recovery of flexural properties during the dry phase. The stiffness recovery was found to be more relevant than the strength.